2021
DOI: 10.1101/2021.02.06.430040
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Repurposing of Synaptonemal Complex Proteins for Kinetochores in Kinetoplastida

Abstract: Chromosome segregation in eukaryotes is driven by a macromolecular protein complex called the kinetochore that connects centromeric DNA to microtubules of the spindle apparatus. Kinetochores in well-studied model eukaryotes consist of a core set of proteins that are broadly conserved among distant eukaryotic phyla. In contrast, unicellular flagellates of the class Kinetoplastida have a unique set of kinetochore components. The evolutionary origin and history of these kinetochores remains unknown. Here, we repo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 98 publications
1
7
0
Order By: Relevance
“…The largest species we observed was determined at ∼209 kDa, which corresponds well to a 1:1 complex of Hop1 and Red1 I743R (theoretical molecular mass of 212 kDa). We observed no species that would correspond to a Red1 tetramer, and we assume this to be a concentration dependent effect, consistent with other components of the synaptonemal complex 4, 77 , to which the C-terminus of Red1 is functionally and evolutionarily related 73 . We also observed masses that correspond to both free Hop1 and free Red1 I743R -MBP (∼81 kDa and ∼140 kDa respectively; theoretical mass 71 kDa and 138 kDa, respectively).…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…The largest species we observed was determined at ∼209 kDa, which corresponds well to a 1:1 complex of Hop1 and Red1 I743R (theoretical molecular mass of 212 kDa). We observed no species that would correspond to a Red1 tetramer, and we assume this to be a concentration dependent effect, consistent with other components of the synaptonemal complex 4, 77 , to which the C-terminus of Red1 is functionally and evolutionarily related 73 . We also observed masses that correspond to both free Hop1 and free Red1 I743R -MBP (∼81 kDa and ∼140 kDa respectively; theoretical mass 71 kDa and 138 kDa, respectively).…”
Section: Resultssupporting
confidence: 82%
“…These data suggest also that, in addition to its described interaction with Hop1 (via its CM, encoded in Red1 340-362 ; see also below 6, 18, 24 ), Red1 appears to encode a Mek1-interaction region. Red1 contains a conserved structured NH2-terminal domain (amino acids 1-340) – likely encoding an Armadillo repeat (ARML) domain and a Pleckstrin homology (PH) domain 61, 72, 73 ( Figure 2c , and see below). This module is followed by a CM sequence (Red1 340-362 ) that mediates interaction with Hop1 17, 24 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed description/manual is available to replicate these analyses/visualizations (see §5 and electronic supplementary material, file S6 for description). The same electronic supplementary material files were also deposited in the FigShare repository at doi:10.6084/ m9.figshare.13725787 [110].…”
Section: Phylogenetic Analysesmentioning
confidence: 99%
“…Importantly, the recent sequencing of the B. mori genome revealed that there is a high degree of sequence homology between silkworm genes and mammalian disease genes (61,(74)(75)(76). Furthermore, Bombyx represents an excellent insect model system for studying meiosis, as SC constituents in non-Drosophilid arthropods are closely aligned with vertebrates, while Drosophila harbor a unique suite of SC factors (77,78). Finally, B. mori Here, we take advantage of the B. mori model system to visualize single chromosome dynamics in meiosis using the Oligopaints technology.…”
Section: Discussionmentioning
confidence: 99%